2016
DOI: 10.1016/j.vaccine.2016.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Trends in compliance with two-dose influenza vaccine recommendations in children aged 6 months through 8 years, 2010–2015

Abstract: Background Children aged 6 months through 8 years may require two doses of influenza vaccine for adequate immune response against the disease. However, poor two-dose compliance has been reported in the literature. Methods We analyzed data for >2.6 million children from six immunization information system (IIS) sentinel sites, and assessed full vaccination coverage and two-dose compliance in the 2010–2015 influenza vaccination seasons. Full vaccination was defined as having received at least the recommended n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…IIS data quality has improved markedly in the past 10 years, [18] and the reliability of these data has been demonstrated through research generating timely estimates of annual influenza coverage for the CDC and state and local public health programs. [19] , [20] The CDC, together with the American Immunization Registry Association (AIRA) and participating IIS, has developed IIS functional standards which include specific criteria for evaluating the data quality of IIS in the US. AIRA collaborates with the IIS community to develop and implement measures and tests to assess IIS alignment with the standards, demonstrating improvement toward and achievement of standards and quality thresholds in the areas of transport, submission, query, clinical decision support, and data quality.…”
Section: Discussionmentioning
confidence: 99%
“…IIS data quality has improved markedly in the past 10 years, [18] and the reliability of these data has been demonstrated through research generating timely estimates of annual influenza coverage for the CDC and state and local public health programs. [19] , [20] The CDC, together with the American Immunization Registry Association (AIRA) and participating IIS, has developed IIS functional standards which include specific criteria for evaluating the data quality of IIS in the US. AIRA collaborates with the IIS community to develop and implement measures and tests to assess IIS alignment with the standards, demonstrating improvement toward and achievement of standards and quality thresholds in the areas of transport, submission, query, clinical decision support, and data quality.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential limit of IV in pediatric age is the need for 2 shots in the younger naïve children, especially in infants who have a very full immunization schedule. Studies showed that the second dose was not always received or delayed far beyond the recommended interval of 28 days (76, 77). There were probably several reasons for incomplete vaccinations, such as schedule complexity, in between-doses frequent infections, difficulties in scheduling a doctor appointment, financial barriers, and lack of provider–parent discussions on the importance of the second dose (78).…”
Section: Limits Of Influenza Vaccination In Pediatric Agementioning
confidence: 99%
“…8 The numerator in the coverage calculation differs across studies. In most, it is (as the CDC defines it) the number of children in the target age group who received a dose of a recommended vaccine [9][10][11][12][13] , while in others it is the number of vaccine doses prescribed or dispensed, 14,15 with the assumption that every vaccine dose prescribed/dispensed equates to one person vaccinated. The numerator may report on (a) a specific number of doses of a vaccine, such as one dose of varicella vaccine 16 or the third dose of HPV vaccine 13 ; or (b) a range of doses, such as children receiving ≥ 1 dose of HPV or influenza vaccine 9,17 ; or (c) the number of children completing the vaccine series.…”
Section: Vaccine Coveragementioning
confidence: 99%
“…"a measure of the frequency with which an event occurs in a defined population in a defined time". 46 For instance Tennis 47 stated, the "vaccination rate was calculated by dividing the number of children vaccinated in a cohort by the total child-days of follow-up within a cohort"; or Lin 11 stated "to calculate vaccination coverage rate, we divided the total number of children who were … vaccinated by the latest Census population estimates in the area for the corresponding year".…”
Section: Vaccination Ratementioning
confidence: 99%